GLOBAL CHALLENGES AND THEIR IMPACT ON THE FORMATION OF INTERNATIONAL ECONOMIC COMPETITIVENESS - BILYK, Ruslana; BILYK, Diana; HAVRYLYUK, Oksana (Herald of Khmelnytskyi National University. Economic sciences, 2024)
This article explores the impact of globalization on the international competitiveness of national economies. It has been determined that a country's ability to compete in the global market is closely linked to the integration of their economies into the global economic space, which significantly shapes their prospects for economic growth, social welfare, and political stability. It is argued that the formation of international competitiveness is driven by a complex of internal and external factors, among which scientific and technological potential, the quality of human capital, the condition of infrastructure, and the effectiveness of government administration hold key positions. Strategies for adapting national economies to the rapidly changing conditions of globalization are proposed, aiming to enhance their capacity for innovation and flexibility in the face of global competition. It is proven that without an effective response to external challenges and active participation in international trade and economic relations, countries will not achieve sustainable socio-economic progress. The role of the institutional environment in ensuring international competitiveness is also outlined, emphasizing the importance of quality governance and legislation, low levels of corruption, and effective protection of property rights. It is found that external factors, such as global economic cycles and geopolitical processes, require countries to have flexible and predictable foreign economic policies to ensure stability and predictability in international relations. A rethinking of international competitiveness through the lens of sustainable development is proposed, requiring a comprehensive approach to innovation, ecological balance, and social responsibility on an international level. It is proven that analyzing international competitiveness in the context of globalization helps to better understand how changes in the global economy affect the strategic decisions of countries regarding their further economic and social development.
Keywords: global challenges; competitiveness; international economy; internal factors; national economy; external factors; effectiveness; investments